2020
DOI: 10.1080/02687038.2020.1795076
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary outcomes from a pilot study of personalised online supported conversation for participation intervention for people with Aphasia

Abstract: Background: Aphasia negatively impacts face-to-face social participation and the difficulties that people experience using the phone exacerbate these challenges in staying in touch with family and friends. Videoconferencing enables multimodal communication, and teamed with supported conversation, could facilitate access to conversation and thereby increase social participation for people with chronic aphasia. Aims: This pilot study examined whether supported conversation provided over Skype could improve peopl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Communication partners, clinicians and industry or research experts were emailed a link to complete electronic participant information and consent forms. Participants with ABI were invited to provide informed written consent using accessible, plain English participant information and consent forms that were adapted to incorporate visual supports and explained via video call by a qualified speech-language pathologist using supported communication strategies [ 41 ]. Screening for the capacity to consent is described in the inclusion criteria (the screening protocol is also included as Multimedia Appendix 1 ) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Communication partners, clinicians and industry or research experts were emailed a link to complete electronic participant information and consent forms. Participants with ABI were invited to provide informed written consent using accessible, plain English participant information and consent forms that were adapted to incorporate visual supports and explained via video call by a qualified speech-language pathologist using supported communication strategies [ 41 ]. Screening for the capacity to consent is described in the inclusion criteria (the screening protocol is also included as Multimedia Appendix 1 ) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Supporting videos explaining each question are available in Multimedia Appendices 3 - 9 . Author MRW, who has living experience of ABI, notes “the video clips that were provided meant we were able to watch it repeatedly to get our ideas out.” Clinician coauthor MW notes that the adaptations made to ensure the accessibility of surveys and videos reflects “the critical nature of these supports in enabling participants with unique needs secondary to ABI to be involved in this research.” For participants with ABI, this survey was administered by a speech-language pathologist (MM) via video teleconference, using supported communication techniques [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, given that policies vary across countries and patients' groups, AHP services are not universally accessible, and it has been found that socio-economic deprivation is associated with barriers in access to AHP services even in contexts where there is universal access to healthcare overall [ 9 , 10 ]. Furthermore, AHP services when provided without serious consideration of the recipients' needs can in their turn increase inequalities [ [11] , [12] , [13] ]. Such findings obscure the landscape around the role of AHPs in reducing health inequalities and stress the need for comprehensive evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Unido a la importante afectación del lenguaje y la comunicación, con consecuencias duraderas según , las PWA informan de diferentes condiciones negativas derivadas de la afasia y que interfieren en su vida cotidiana: una menor participación y disminución de la satisfacción en las relaciones y actividades sociales, aislamiento, dificultad para controlar sus emociones, dificultad con las actividades de autocuidado diario, dependencia física, pérdida de autonomía, cambios en la dinámica y roles familiares y en general, una disminución en la calidad de vida (CdV) , Cruice, Woolf, Caute, Monnelly, Wilson y Marshall, 2020Fotiadou, Northcott, Chatzidaki y Hilari, 2014). Además, estas condiciones afectan en mayor proporción a las PWA que a los supervivientes de ACV sin afasia (Mizoon, Lyden, Brady y VISTA, 2015).…”
unclassified